(untitled) (Journal of The Colloquium for Information Systems Security Education, 2016)
The academic discipline of cybersecurity is still in its formative years. One area in need of improvement is teaching cybersecurity students adversarial thinking—an important academic objective that is typically defined as “the ability to think like a hacker.” Working from this simplistic definition makes framing student learning outcomes difficult, and without proper learning outcomes, it is not possible to create appropriate instructional materials. A better understanding of the concept of adversarial thinking is needed in order to improve this aspect of cybersecurity education. This paper sheds new light on adversarial thinking by exploring it through the lens of Sternberg’s triarchic theory of intelligence. The triarchic theory’s division of the intellect into the analytical, creative, and practical components provides a comprehensive framework for examining the characteristic thought processes of hackers. This exploration produces a novel, multidimensional definition of adversarial thinking that leads immediately to three clearly defined learning outcomes and to some new ideas for teaching adversarial thinking to cybersecurity students.